How to achieve annulment of an arbitral award for Tribunal corruption? Learned lessons of case ONCOSERV - Talavera Cano, Andrés (2017)
The Arbitration is a one – time process instance in which the parties submit in an arbitrator to settle a dispute between them. The annulment of this process occurs through an exceptional remedy before the judicial court which finds sustenance in a serious violation of due process.In the present article, the author analyzes the case “Oncoserv v. Regional Government of Arequipa“, which has set a milestone in the history of Arbitration in Peru due to its unfortunate link with corruption. Its relevance lies in the application of the annulment remedy for an issue other than the notification or right to defense, such as corruption, which has had a great impact on national law.